Organizational Culture and Its Impact on Employee Performance - Iskamto, Dedi (International Journal of Management and Digital Business, 2023)
This study aims to analyze the influence of organizational culture on employee performance, explore the factors that influence an effective organizational culture. This research uses quantitative methods. Processing and hypothesis testing using SPSS version 25. The research location is a government institution in Riau Province. The population in the study were all office employees. In this study, sampling used a saturated sample, that is, if the population is smaller than 100 people, then the population is used as a sample, so that the number of samples studied is 35 employees. the results indicated that Organizational culture significant effect on performance. . It was found that Organizational Culture contributed 26.6% to employee performance, the remaining 73.4% was influenced by factors not examined in this study.